Analysis Of Work Ethics And Work Stress On Motivation Mediated Employee Performance At The JW Marriott Hotel - Frans Willem; Yohny Anwar (Yayasan Multidimensi Kreatif, 2025)
This research aims to test and analyze the influence of work ethics and work stress on employee performance and test and analyze the influence of work ethics and work stress on employee performance through motivation. This research was conducted at the JW Mariot Hotel Medan. The sample used in this study was 70 respondents. This study was analyzed using SMART PLS. From the results of the study, it was found that work ethics had a positive and significant effect on employee motivation at JW Mariot Medan. Work Stress has a positive and significant effect on employee motivation at JW Mariot Medan. Motivation has a positive and significant effect on employee performance at JW Mariot Medan. Work ethics have a positive and significant effect on employee performance at JW Mariot Medan. Work Stress has a positive and significant effect on employee performance at JW Mariot Medan.Work ethics has a positive and significant effect on employee performance at JW Mariot Medan which is mediated by motivation. Work stress has a positive and significant effect on employee performance at JW Mariot Medan which is mediated by motivation.